Organic carbon preservation promoted by aromatic compound-iron complexes through manure fertilization in red soil - Wen, Yunjie; Wen, Jiong; Wang, Qi; Bai, Lingyu; Wang, Yanan; Su, Shiming; Wu, Cuixia; Zeng, Xibai (Journal of soils and sediments, 2021)
Purpose This study was aimed at evaluating the effect of manure fertilization on organo-mineral complexes based on unfertilized (CK) and 5-year manure fertilization (M) in red soils (ultisols). Materials and methods Sequential density fractionation was adopted to obtain particular organic matter (POM, < 1.8 g cm −3 ) and mineral-associated organic matter (1.8–2.2 g cm −3 (MOM 1.8–2.2 ); 2.2–2.6 (MOM 2.2–2.6 ); > 2.6 (MOM > 2.6 )), which were demineralized by hydrofluoric acid (HF). The HF-dissolved organic carbon (OC) was identified as mineral bound OC, and was characterized by comparing the band area of Fourier transform infrared spectroscopy before and after 10% HF demineralization. Results and discussion Manure fertilization significantly increased the OC and nitrogen contents of bulk soil, POM, MOM 1.8–2.2 , and MOM 2.2–2.6 , but did not affect MOM > 2.6 . About 82.9–86.1% soil OC was retained by MOM 1.8–2.2 and MOM 2.2–2.6 dominated with iron (Fe) and aluminum oxides and phyllosilicates, in which HF-dissolved OC was significantly positively correlated with poorly crystalline (Fe o ) ( R 2 = 0.61, P < 0.01) and organically complexed (Fe p ) Fe contents ( R 2 = 0.45, P < 0.05). Moreover, the Fe o and Fe p contents were higher in M than in CK ( P < 0.05), and significantly negatively correlated with the reduction of aromatic C (M had more reduction than CK) following HF demineralization in MOM 1.8–2.2 and MOM 2.2–2.6 ( P < 0.05), indicating Fe bound OC was mainly aromatic C. The quartz and feldspar-dominated MOM > 2.6 was composed of aromatic C, amide N, and polysaccharides, not being affected by fertilization. Conclusions Our results suggested that manure fertilization promotes organo-mineral association, particularly for aromatic compound-Fe complexes, contributing to OC preservation in red soils.